Preparation method of silicon-carbon material and current collector

By using carbon nanotube tubes to coat nanosilicon in lithium-ion battery negative electrode materials, the problem of volume expansion of silicon negative electrode materials during charging and discharging is solved, the cycle stability and safety of the battery are improved, and the internal resistance is reduced.

CN119890238APending Publication Date: 2025-04-25DONG JIAN CHU NA (SHANG HAI) JI SHU YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510090241.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The energy density of existing lithium-ion battery anode materials is limited, and the volume expansion of the silicon anode materials during charging and discharging leads to the material breakage and powderization, reducing the cycle life and safety of the battery.

Method used

The nano-silicon is coated with carbon nanotube tubes, and the nano-silicon is embedded in the internal structure of the carbon nanotube. Through multiple temperature zone control conditions, a continuous carbon nanotube tube is generated in the high temperature zone to alleviate the expansion of the silicon volume, and a silicon/carbon nanotube composite film is applied on the copper foil to increase the contact area between the current collector and the negative electrode material.

Benefits of technology

It effectively alleviates the problem of silicon volume expansion, improves the cycle stability and safety of the battery, and significantly increases the contact area between the current collector and the negative electrode material, reducing internal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251292930000071
    Figure BDA0005251292930000071
Patent Text Reader

Abstract

The invention relates to a preparation method of a silicon-carbon material and a current collector, and aims to solve the problem of limited energy density of an existing lithium ion battery negative electrode material. According to the method, the temperatures of different temperature zones are controlled in a vertical furnace, a carbon source, a catalyst, silane, hydrogen and carrier gas are introduced into a reaction furnace, products are collected on rollers through traction of iron wires, and the silicon / carbon nanotube material is formed. And then, carrying out acid pickling and densification treatment to obtain a silicon / carbon nanotube composite film, coating the silicon / carbon nanotube composite film with a binder, and pasting the silicon / carbon nanotube composite film on a copper foil to prepare the silicon-carbon negative electrode current collector. The silicon-carbon material prepared by the method has excellent electrochemical performance and good cycle stability, can effectively relieve the problem of silicon volume expansion, and improves the cycle life and safety of the battery. By accurately controlling material synthesis conditions, the method provides a novel silicon-carbon negative electrode material and a composite current collector for the development of high-performance lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of new energy battery materials, and more specifically to the preparation of silicon carbon and current collectors. Background Art

[0002] Lithium-ion batteries have become an important energy solution for portable electronic devices, electric vehicles, and large-scale energy storage systems due to their high energy density, long cycle life, and environmental friendliness. However, existing lithium-ion battery anode materials, such as graphite, have limited theoretical specific capacity and are difficult to meet the market demand for batteries with higher energy density.

[0003] In order to break through this limitation, researchers have been exploring new negative electrode materials with higher theoretical specific capacity. As a material with high theoretical specific capacity, silicon is considered to be an ideal negative electrode material for next-generation lithium-ion batteries. However, silicon undergoes significant volume expansion during charging and discharging, which can cause the material to crack and pulverize, thereby reducing the cycle life and safety of the battery.

[0004] In order to solve the volume expansion problem of silicon negative electrode materials, researchers have tried a variety of methods, including preparing silicon-carbon composite materials. Silicon-carbon composite materials combine silicon nanoparticles with carbon materials, using the elasticity and conductivity of carbon materials to buffer the volume expansion of silicon, thereby improving the cycle stability of the battery. In addition, carbon materials can also improve the conductivity of the electrode, further improving the overall performance of the battery. Summary of the invention

[0005] The present invention aims to provide a method for preparing a silicon-carbon negative electrode material and a current collector. The method uses a carbon nanotube tube to coat nano-silicon, and embeds nano-silicon into the internal structure of the carbon nanotube, which is more conducive to alleviating the expansion of silicon volume. The carbon nanotube is a continuous structure, and there is no need to worry about the material pulverization problem. In addition, because a layer of carbon coating (silicon / carbon nanotube) is attached to the surface of the copper foil, the contact area between the current collector and the negative electrode material can be significantly increased, and the internal resistance can be reduced.

[0006] The technical solution adopted by the present invention is a method for preparing a silicon-carbon material and a current collector, and the preparation method is as follows:

[0007] (1) A vertical furnace with five temperature sections is set as a reaction furnace, and the five temperature sections are low temperature section, medium temperature section, high temperature section, medium temperature section, and low temperature section from top to bottom (the five temperature sections can better promote heat convection);

[0008] (2) introducing a carbon source, a catalyst, silane, hydrogen and a carrier gas into a reaction furnace, and pulling the obtained product onto a collecting roller through a metal wire at the bottom of the furnace to obtain a silicon / carbon nanotube material;

[0009] (3) After the reaction furnace cools to room temperature, the silicon / carbon nanotube material obtained in step (2) is taken out, densified, and subjected to acid washing to obtain a silicon / carbon nanotube composite film;

[0010] (4) After the silicon / carbon nanotube composite film is dried, a binder is coated on one side and the film is pasted on a copper foil to obtain a silicon-carbon negative electrode current collector.

[0011] In the step (1), the temperature of the low temperature zone is 450-600°C, the temperature of the medium temperature zone is 600-1000°C, and the temperature of the high temperature zone is 1000-1700°C.

[0012] In the step (2), the carbon source is a gaseous carbon source, the catalyst is one or more compounds containing iron, cobalt and nickel, and the carrier gas is nitrogen or argon.

[0013] The catalyst is sublimated and enters the reaction furnace through the carrier gas.

[0014] In the step (2), the silane inlet rate in the reaction furnace is 100-300 ml / min, the carbon source inlet rate is 50-100 ml / min, the hydrogen inlet rate is 10-50 ml / min, the carrier gas inlet rate is 10-50 ml / min, and the sublimated catalyst inlet rate is 2-5 ml / min.

[0015] In the step (2), the collecting roller is made of polytetrafluoroethylene and is placed at the lower end of the reaction furnace, 30 to 40 cm away from the outlet of the tube tail.

[0016] The densification treatment in step (3) is to immerse the silicon / carbon nanotube material in an ethanol or acetone solution.

[0017] After densification, the thickness of the silicon / carbon nanotube composite film is 2 to 3 μm.

[0018] In the step (3), the pickling is performed using nitric acid and hydrochloric acid.

[0019] Silane decomposes into nano-silicon with a size of 5 to 10 nm in the low temperature zone; the catalyst completely decomposes in the medium temperature zone to release metal particles; the carbon source self-assembles through the catalyst in the high temperature zone to form a continuous carbon nanotube sleeve.

[0020] The present invention aims to solve the problem of limited energy density of existing negative electrode materials for lithium-ion batteries. The method controls the temperature of different temperature zones in a vertical furnace, passes a carbon source, a catalyst, silane, hydrogen and a carrier gas into the reaction furnace, and collects the product on a roller by traction with an iron wire (metal wire) to form a silicon / carbon nanotube material. Subsequently, a silicon / carbon nanotube composite film is obtained by pickling and densification treatment, and the film is coated with a binder and pasted on a copper foil to form a silicon-carbon negative electrode current collector. The silicon-carbon material prepared by the method has excellent electrochemical properties and good cycle stability, can effectively alleviate the problem of silicon volume expansion, and improve the cycle life and safety of the battery. By precisely controlling the material synthesis conditions, the method provides a new type of silicon-carbon negative electrode material and composite current collector for the development of high-performance lithium-ion batteries.

[0021] Beneficial effects of the present invention:

[0022] The present invention adopts multiple temperature zones, and first deposits nano-silicon by CVD, and the nano-silicon enters the medium and high temperature zone under the action of gravity and carrier gas. In the high temperature zone, by controlling the flow rate of hydrogen, the carbon source partially generates continuous carbon nanotube tubes under the action of the catalyst, and the other part generates amorphous carbon. At this time, in the carbon nanotubes, the carbon nanotubes will cover the nano-silicon particles. The amorphous carbon can properly fill the pores during the reaction process, and synergize with the graphite layer coated by the processed pole piece to prevent silicon from directly contacting the electrolyte. It is also convenient for storage and secondary processing after densification. The material is in a continuous film, and there is no need to worry about subsequent pulverization caused by charging and discharging, which also provides a method for the preparation of thick pole pieces. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical scheme and technical effect of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is clearly and completely described. The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments. In conjunction with the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer; if the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0024] In the description of the present invention, the term "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0025] In the description of the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0026] It should be understood that the weight of the relevant components mentioned in the embodiments of the present invention can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present invention is proportionally enlarged or reduced, it is within the scope disclosed by the present invention. Specifically, the weight described in the embodiments of the present invention can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0027] In addition, unless the context clearly uses otherwise, the expression of the singular form of a word should be understood to include the plural form of the word. The term "includes" or "having" is intended to specify the existence of a feature, quantity, step, operation, element, part or combination thereof, but is not used to exclude the existence or possible addition of one or more other features, quantities, steps, operations, elements, parts or combinations thereof.

[0028] The technical solution adopted by the present invention is a method for preparing a silicon-carbon negative electrode material and a current collector, and the specific implementation steps are as follows:

[0029] Step 1: Set up a vertical furnace with five temperature zones, the five temperature zones from top to bottom are low temperature zone, medium temperature zone, high temperature zone, medium temperature zone, and low temperature zone;

[0030] Step 2: introducing a carbon source, a catalyst, silane, hydrogen, and a carrier gas into a reaction furnace, and pulling the obtained product onto a collecting roller through a wire at the bottom of the furnace to obtain a silicon / carbon nanotube material;

[0031] Step 3: After the reaction furnace is cooled to room temperature, the silicon / carbon nanotube material is taken out and subjected to acid washing and densification treatment to obtain a silicon / carbon nanotube composite film;

[0032] Step 4: After drying, a binder is applied to one side of the silicon / carbon nanotube composite film and the film is pasted on a copper foil to obtain a silicon-carbon negative electrode current collector.

[0033] The present invention adopts multiple temperature zones, and first deposits nano-silicon by CVD, and the nano-silicon enters the medium and high temperature zone under the action of gravity and carrier gas. In the high temperature zone, by controlling the flow rate of hydrogen, the carbon source partially generates continuous carbon nanotube tubes under the action of the catalyst, and the other part generates amorphous carbon. At this time, in the carbon nanotubes, the carbon nanotubes will cover the nano-silicon particles. The amorphous carbon can properly fill the pores during the reaction process, and synergize with the graphite layer coated by the processed pole piece to prevent direct contact between silicon and the electrolyte, and it is convenient for storage and secondary processing after densification. The material is in a continuous film, and there is no need to worry about subsequent pulverization caused by charging and discharging, which also provides a method for the preparation of thick pole pieces.

[0034] The mass ratio of silicon and carbon (amorphous carbon and CNT) in the finally prepared silicon carbon is 1 to 5:1, and the thickness of the silicon / carbon nanotube composite film is 2 to 3 μm. Embedding nano-silicon into the internal structure of carbon nanotubes is more conducive to alleviating the expansion of silicon volume, and the carbon nanotubes are a continuous structure, so there is no need to worry about material pulverization.

[0035] Specifically, the diameter of the carbon nanotubes is 1 to 10 nm and the length is 10 to 60 μm;

[0036] Specifically, the size of nano-silicon is 5 to 10 nm (the size after silane is decomposed in a low temperature region);

[0037] Specifically, the silane inlet rate is 100-200 ml / min, the carbon source inlet rate is 50-100 ml / min, the hydrogen inlet rate is 10-20 ml / min, the carrier gas inlet rate is 10-50 ml / min, and the sublimated catalyst inlet rate is 2-5 ml / min;

[0038] Specifically, the method used for the densification treatment of the silicon / carbon nanotube composite film is immersion in an ethanol solution;

[0039] Specifically, the pickling is performed by washing with concentrated nitric acid and concentrated hydrochloric acid in a volume ratio of 1:3;

[0040] In order to enable those skilled in the art to clearly understand the implementation details and operations of the present invention, and to significantly demonstrate the improved performance of the embodiments of the present invention, the above technical solutions are illustrated by multiple embodiments below.

[0041] Example 1

[0042] A method for preparing a silicon-carbon negative electrode material and a current collector, the specific implementation steps are as follows:

[0043] Step 1: Set up a vertical furnace with five temperature zones, with the five temperature zones set at 550°C, 900°C, 1200°C, 900°C, and 600°C from top to bottom;

[0044] Step 2: Gaseous toluene at 170 ml / min, ferrocene after sublimation at 2.5 ml / min, silane at 150 ml / min, hydrogen at 12 ml / min, and argon at 30 ml / min are introduced into the reactor. After a period of time, the obtained product is pulled from the bottom of the furnace to a collecting roller (the collecting roller is made of polytetrafluoroethylene and is placed at the lower end of the reactor, 30 to 40 cm away from the outlet of the tube tail) through a wire to obtain a silicon / carbon nanotube material, and the measured silicon content is 62%;

[0045] Step 3: After the reaction furnace is cooled to room temperature, the silicon / carbon nanotube material is taken out, immersed in ethanol for densification treatment, and then acid-washed (washed with concentrated nitric acid and concentrated hydrochloric acid in a volume ratio of 1:3) to obtain a silicon / carbon nanotube composite film;

[0046] Step 4: After drying, one side of the silicon / carbon nanotube composite film is coated with an SBR binder and pasted on a copper foil to obtain a silicon-carbon negative electrode current collector;

[0047] Step 5: Scrape a graphite layer on the surface of the composite current collector. The graphite layer uses graphite: CMC: SP = 93: 5: 2, and the thickness of the graphite layer is 40 μm.

[0048] Comparative Example 1

[0049] The silicon-carbon negative electrode (purchased powder material) and graphite were mixed in proportion, and the specific capacity after mixing was adjusted to be similar to that in Example 1, and a negative electrode slurry was prepared and coated on a copper foil.

[0050] Performance Testing

[0051] Button cells were made based on the silicon-carbon composite negative electrode materials provided in the above embodiments and comparative examples, and their electrochemical performance was tested.

[0052] The negative electrode slurry is coated on a copper foil, dried and rolled to obtain a negative electrode sheet; the electrolyte is a solution with LiPF6 and 10% FEC as electrolytes, with a concentration of 1 mol / L, wherein the solvent is a mixed solution of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene film.

[0053] In an argon glove box, the button cell was assembled on a Xinwei CT-4008Tn battery tester to carry out an electrochemical cycle performance test, with a charge and discharge voltage range of 0.01 V to 2.0 V and a charge and discharge rate of 0.1C.

[0054] In addition, the button cell was also subjected to a capacity retention rate test. The specific test process was as follows: after completion, the battery was cycled three times at 0.1C (recording the average specific capacity Q1), 0.3C, 0.5C, 1C, 2C, and 3C, and then cycled three times at a rate of 0.1C (recording the average specific capacity Q2). The capacity retention rate = Q2 / Q1×100%.

[0055] Table 1

[0056]

[0057] It can be seen from the table that the material performance of the present invention has higher stability than the silicon-carbon negative electrode prepared by the traditional method.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a silicon-carbon material and a current collector, characterized in that: The preparation method is as follows: (1) A vertical furnace with five temperature zones is used as a reaction furnace. The five temperature zones are low temperature zone, medium temperature zone, high temperature zone, medium temperature zone, and low temperature zone from top to bottom; (2) introducing a carbon source, a catalyst, silane, hydrogen and a carrier gas into a reaction furnace, and pulling the obtained product onto a collecting roller through a metal wire at the bottom of the furnace to obtain a silicon / carbon nanotube material; (3) After the reaction furnace cools down to room temperature, the silicon / carbon nanotube material obtained in step (2) is taken out, densified, and subjected to acid washing to obtain a silicon / carbon nanotube composite film; (4) After the silicon / carbon nanotube composite film is dried, a binder is coated on one side and the film is pasted on a copper foil to obtain a silicon-carbon negative electrode current collector.

2. A method for preparing a silicon-carbon material and a current collector according to claim 1, characterized in that: In the step (1), the temperature of the low temperature zone is 450-600°C, the temperature of the medium temperature zone is 600-1000°C, and the temperature of the high temperature zone is 1000-1700°C.

3. The method for preparing a silicon-carbon material and a current collector according to claim 1, characterized in that: In the step (2), the carbon source is a gaseous carbon source, the catalyst is one or more compounds containing iron, cobalt, and nickel, and the carrier gas is nitrogen or argon.

4. A method for preparing a silicon-carbon material and a current collector according to any one of claims 1 or 4, characterized in that: The catalyst is sublimated and enters the reaction furnace through the carrier gas.

5. The method for preparing a silicon-carbon material and a current collector according to claim 1, characterized in that: In the step (2), the silane inlet rate in the reaction furnace is 100-300 ml / min, the carbon source inlet rate is 50-100 ml / min, the hydrogen inlet rate is 10-50 ml / min, the carrier gas inlet rate is 10-50 ml / min, and the sublimated catalyst inlet rate is 2-5 ml / min.

6. A method for preparing a silicon-carbon material and a current collector according to claim 1, characterized in that: In the step (2), the collecting roller is made of polytetrafluoroethylene and is placed at the lower end of the reaction furnace, 30 to 40 cm away from the outlet of the tube tail.

7. The method for preparing a silicon-carbon material and a current collector according to claim 1, characterized in that: The densification treatment in step (3) is to immerse the silicon / carbon nanotube material in an ethanol or acetone solution.

8. A method for preparing a silicon-carbon material and a current collector according to claim 7, characterized in that: After densification, the thickness of the silicon / carbon nanotube composite film is 2~3μm.

9. The method for preparing a silicon-carbon material and a current collector according to claim 1, characterized in that: In step (3), the pickling is performed using nitric acid and hydrochloric acid.

10. A method for preparing a silicon-carbon material and a current collector according to claim 1, characterized in that: Silane decomposes into nano-silicon with a size of 5~10nm in the low temperature zone; the catalyst completely decomposes in the medium temperature zone to release metal particles; the carbon source self-assembles through the catalyst in the high temperature zone to form a continuous carbon nanotube sleeve.